The adoption and use of internet banking by Malaysian consumers: An empirical investigation - Lim, Chee Leong (2006)
Bank Negara Malaysia (BNM) removed the restrictions on providing banking transactions through the Internet on June 2000.This has enabled Internet banking to be emerged as a popular financial service delivery platform in Malaysia. The success of this new distribution channel for banking products and services depends on the adoption rate by Malaysian consumers.Thus, this paper examines the key determinants that critically affect consumers’ decision in adopting Internet banking.It also aims at forming a model describing the relationships among these determinants in order to evaluate which determinants have a direct/ indirect impact on Internet banking adoption.It has revealed that convenience and accessibility of the Internet banking service have a significant impact on the adoption.In addition, simplification and ease of use of Internet banking, security and trust concerns as well as consumers’ prior technology experience are found affecting their decision indirectly in adopting Internet banking.Finally, implications of results were highlighted and future research directions were outlined.